Taurine Prevented Biochemical Alterations in Chronic Restraint-Stressed Wistar Rats - Iliya, Ezekiel; Agnes Igimi, Odey; Stephen Olawale, Ajayi; Ejike, Daniel Eze; Obioha, Mary (FUW Trends in Science & Technology Journal, www.ftstjournal.com, 2023)
Stress has the potential of altering physiological homeostasis. The body’s ability to cope under stressful stimuli is a vital determinant of health and disease conditions. In this study, Wistar rats were weighed and randomly allocated into four groups (n=6): group A: control (1 ml/kg of distilled water), group B: (100 mg/kg of taurine), group C: (200 mg/kg taurine) and group D: received 400 mg/kg taurine. The treatments were administered once daily (60 minutes) prior to the commencement of the stress sessions by oral gavage for 21 days. During the experiment, concentration of malondialdehyde (MDA) and activity of acetylcholinesterase were evaluated in the fore brain homogenate samples. Other biochemical parameters assayed in the serum were the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). The result revealed significant (p < 0.05) increase in the brain AChE activity in taurine 100 mg/kg when compared to the control group. Also there was significant (p < 0.05) increase in total protein in all the taurine treated groups but a significant (p < 0.05) decrease in albumin in the group that was administered 100 mg/kg taurine when compared with 200 and 400 mg/kg groups. There was no significant (p > 0.05) difference in the serum MDA concentration and activities of SOD, CAT and GPx in all the taurine treated groups when compared with the control group. The results of this study suggested that, taurine has immense potential as an anti-stress agent of great therapeutic relevance